A cooperação em crianças de rede pública de Natal/RN:uma abordagem evolucionista - Alencar, Anuska Irene de (2008)
Cooperation is a well known behavior and influenced by all cultures. Probably selective pressures brought advantages to individuals that cooperate, and then this behavior is current in human societies. Most of it is studied about cooperation and natural selection was understood by the game theory, a mathematical approach that helps to understand the conflict and cooperation. We believe that natural selection and game theory could facilitate understanding these behaviors and two theoretical articles were written regarding this view. It was also found that most of data about cooperation was obtained in (with) adults. Since game theory is effective to understand this phenomenon, and to be used and understood, two games were used with five and eleven year old children: the common pool and public goods games. The results are presented in four empirical articles. We found that children respond to social dilemmas of game theory like the adults do. They adjust their rounds regarding the feedback obtained of their partness; in the beginning they cooperate and reduce the degree of cooperation along (throughout) the following session; in the absence of punition the level of opportunism increased, mainly in larger groups; boys and girls behave differently when donate. This research suggest that cooperation has an evolutionary basis in human and it is since earlier in the behavioral pattern shown by adults.